The perceptual and behavioral influence on dental professionals from the noise in their workplace. (April 2020) - Ma, Kuen Wai; Mak, Cheuk Ming; Wong, Hai Ming
Highlights: The acoustical influence of noise in dental workplaces was investigated. Psychoacoustic metrics in different statistical noise levels were assessed. Noise sensitivity and job-performance drop are affected by the loudness of noise. The health risk perceptions can be divided into loudness- or sharpness-related. Avoidance of noise is influenced by the subjects' health state and background noise. Abstract: A long-term exposure to the high-frequency dental noise is a potential hazard to the health of dental professionals and the quality of oral health service provisions. This study aims to thoroughly investigate the influence of an acoustic environment on the perceptions and behaviors of dental professionals. A multidimensional sound quality assessment that comprises the objective measurements of the acoustic and psychoacoustic metrics in different statistical levels and a self-administrated questionnaire was conducted in the Prince Philip Dental Hospital of Hong Kong. The results indicate that the dental professionals' noise sensitivity and job-performance drops are mainly affected by loudness of noise. Moreover, two types of health risk perceptions, loudness-related and sharpness-related, were found to be associated with a health state of dental professionals. Also, a higher chance of having health-mediated avoidance was found for the dental professionals who had a worse health state and worked in a noisier workplace. These findings provide new knowledge on the development of a health-supportive acoustic environment.